Tuneable and switchable dual wavelength laser diodes using fibre Bragg grating external cavities - Reilly, Simon Philip (Cranfield University, 2003)
This thesis describes two external cavity laser diode designs. The first utilises a Bragg grating fabricated in highly biréfringent optical fibre and offers, through the use of a waveplate, the ability to switch between modes that are separated in both polarisation and wavelength, due to the differing refractive index in either eigenmode. The laser offers three stabilised states of operation, single mode operation for either axis of the fibre, or a third state in which both modes lase simultaneously with a wavelength separation of 0.3 nm. The application of transverse strain on the fibre Bragg grating was also demonstrated as a method of tuning the wavelength separation between these modes. The second external cavity laser design utilises two spatially and spectrally separate Bragg gratings fabricated in mono-mode fibre. This allows two longitudinal modes corresponding to the Bragg wavelengths to oscillate simultaneously. The application of longitudinal strain allowed either fibre Bragg grating to be tuned, thus generating a stabilised tuneable beat frequency, which was demonstrated between 130 GHz - 2.28 THz. A three fibre Bragg grating laser is also presented which allowed three modes to oscillate simultaneously. Both the laser based on a Bragg grating fabricated in highly biréfringent fibre and the laser based on multiple Bragg gratings fabricated in single mode fibre demonstrated reduced injection current threshold and mode hop free operation over the full injection current range. A practical application for the two fibre Bragg grating lasers is presented where the properties o f independently tuneable dual wavelength operation are used to interrogate a miniature fibre Fabry-Perot sensor. The wavelength separation o f the two oscillating modes can be tuned to reach a point of quadrature for the sensor cavity. A sensing system demonstrating this technique is presented which detected vibrations up to 500 Hz in cavities of 16-34 pm.